Military blast exposure, ageing and white matter integrity - Trotter, Benjamin B. (Brain, 2015)
Mild traumatic brain injury, or concussion, is associated with a range of neural changes including altered white matter structure. There is emerging evidence that blast exposure—one of the most pervasive causes of casualties in the recent overseas conflicts in Iraq and Afghanistan—is accompanied by a range of neurobiological events that may result in pathological changes to brain structure and function that occur independently of overt concussion symptoms. The potential effects of brain injury due to blast exposure are of great concern as a history of mild traumatic brain injury has been identified as a risk factor for age-associated neurodegenerative disease. The present study used diffusion tensor imaging to investigate whether military-associated blast exposure influences the association between age and white matter tissue structure integrity in a large sample of veterans of the recent conflicts (n = 190 blast-exposed; 59 without exposure) between the ages of 19 and 62 years. Tract-based spatial statistics revealed a significant blast exposure × age interaction on diffusion parameters with blast-exposed individuals exhibiting a more rapid cross-sectional age trajectory towards reduced tissue integrity. Both distinct and overlapping voxel clusters demonstrating the interaction were observed among the examined diffusion contrast measures (e.g. fractional anisotropy and radial diffusivity). The regions showing the effect on fractional anisotropy included voxels both within and beyond the boundaries of the regions exhibiting a significant negative association between fractional anisotropy and age in the entire cohort. The regional effect was sensitive to the degree of blast exposure, suggesting a ‘dose-response’ relationship between the number of blast exposures and white matter integrity. Additionally, there was an age-independent negative association between fractional anisotropy and years since most severe blast exposure in a subset of the blast-exposed group, suggesting a specific influence of time since exposure on tissue structure, and this effect was also independent of post-traumatic stress symptoms. Overall, these data suggest that blast exposure may negatively affect brain-ageing trajectories at the microstructural tissue level. Additional work examining longitudinal changes in brain tissue integrity in individuals exposed to military blast forces will be an important future direction to the initial findings presented here.